(untitled) (Filološke pripombe, 2019)
The article deals with the institutionalisation ofart history as a »scientific discipline« at the universities in thegerman-speaking countries at the beginning of the 20th century. Alois Riegl andHeinrich Wölfflin, basing themselves on the humboldtian notions ofhistoriography and philology, posited that the art historian’s task is toexplore the artistic form (as opposed to the content of an artefact) and,through that, the worldview (of a certain people) which the artefactdemonstrates.